Effect of fluid-shale interactions on shales micromechanics: Nanoindentation experiments and interpretation from geochemical perspective - Zeng, Lingping; Akhondzadeh, H.; Iqbal, Muhammad Atif; Keshavarz, A.; Rezaee, Reza; Xie, Sam (ELSEVIER SCI LTD, 2022)
Multi-stage hydraulic fracturing combined with horizontal drilling has been widely implemented to enhance oil/gas production from shale reservoirs. One method of reservoir stimulation is to use low-salinity fracturing fluid that mixes with existing high-salinity formation brine. This process either activates existing natural fractures or generates new fractures thus enhances reservoir communication. However, it is still unclear how the in-situ geochemistry change would affect shale surface energy and fracture/micro-fracture propagation, and far less research has investigated the effect of salinity on shale micromechanics. This impedes the proper evaluation of hydraulic fracturing influence on the stability of shale reservoirs with different mineralogy. In this study, the strength of shale samples with different composition at different saturation conditions were measured using nano-indentation techniques together with atomic force microscopy (AFM) and scanning electron microscopy (SEM). In addition, geochemical modelling with the combination of surface complexation and disjoining pressure isotherm were performed to examine the role of physicochemical reactions on shale micromechanical properties. Nano-indentation tests confirm that brine saturation can decrease samples’ indentation moduli regardless of mineralogy. We also found that decreasing salinity would further decrease indentation modulus of calcite-, quartz- and illite-rich shale samples by 43.8%, 19.2%, and 33.3%, suggesting that rock micromechanics are indeed affected by the geochemistry. Compared to dry condition, calcite- and quartz-rich shales have greater indentation moduli reduction after low salinity brine saturation (64.3% and 45.4%) than the illite-rich sample (32.2%), indicating that fluid-rock interactions associated with shale micromechanics are also influenced by mineralogy. Thermodynamics calculation shows that the shift of the disjoining pressure isotherm from strongly negative to positive likely plays an important role in shale weakening rather the mineral dissolution before and after water saturation. Taken together, these findings provide a new understanding of surface energy induced micromechanics of shale through geochemical modelling together with thermodynamics.